Pendidikan Islam Anak Usia Dini dalam Arus Modernisasi antara Adaptasi dan Pelestarian Nilai Keislaman - Mahdi, Nur Imam (AUD Cendekia: Journal of Islamic Early Childhood Education, 2024)
This study aims to analyze the dynamics of Islamic Early Childhood Education in the Era of Modernization at RA Islamic Center, focusing on three main aspects: the forms of adaptation to modernization, strategies for preserving Islamic values, and the balance between innovation and Islamic principles in learning. The research employs a qualitative method with a phenomenological approach, involving 10 informants consisting of the principal, teachers, and parents. Data were collected through in-depth interviews and analysis of curriculum documents and institutional activity reports. The results indicate that RA Islamic Center implements a selective and integrative adaptation model in responding to modernization. Modernization is not perceived as a threat but as an opportunity to enhance the quality of learning through the use of technology, creativity, and collaboration while remaining grounded in Islamic values. Learning innovations such as thematic projects, interactive digital media, and contextual methods are utilized to enrich children’s learning experiences. The preservation of Islamic values is maintained through regular worship practices, teacher role modeling, the integration of Islamic teachings into play-based activities, and strong cooperation with parents. The study concludes that the balance between modernity and spirituality can be achieved through the Selective-Integrative Adaptation Model, which employs innovation as a means to strengthen Islamic values. Theoretically, this research enriches contemporary Islamic education studies, while practically, it provides guidance for Islamic early childhood institutions to face modern challenges without losing their Islamic identity.